Treatment as Prevention for Hepatitis C (TraP Hep C) – a nationwide elimination programme in Iceland using direct‐acting antiviral agents. (7th March 2018) - Olafsson, S.; Tyrfingsson, T.; Runarsdottir, V.; Bergmann, O. M.; Hansdottir, I.; Björnsson, E. S.; Johannsson, B.; Sigurdardottir, B.; Fridriksdottir, R. H.; Löve, A.; Hellard, M.; Löve, T. J.; et al.
Abstract: A nationwide programme for the treatment of all patients infected with hepatitis C virus (HCV) was launched in Iceland in January 2016. By providing universal access to direct‐acting antiviral agents to the entire patient population, the two key aims of the project were to (i) offer a cure to patients and thus reduce the long‐term sequelae of chronic hepatitis C, and (ii) to reduce domestic incidence of HCV in the population by 80% prior to the WHO goal of HCV elimination by the year 2030. An important part of the programme is that vast majority of cases will be treated within 36 months from the launch of the project, during 2016–2018. Emphasis is placed on early case finding and treatment of patients at high risk for transmitting HCV, that is people who inject drugs (PWID), as well as patients with advanced liver disease. In addition to treatment scale‐up, the project also entails intensification of harm reduction efforts, improved access to diagnostic tests, as well as educational campaigns to curtail spread, facilitate early detection and improve linkage to care. With these efforts, Iceland is anticipated to achieve the WHO hepatitis C elimination goals well before 2030. This article describes the background and organization of this project. Clinical trial number: NCT02647879 .